2021
DOI: 10.3390/ijerph18030925
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Mindfulness, Purpose in Life, Happiness, Anxiety, and Depression: Testing a Mediation Model in a Sample of Women

Abstract: Mindfulness is connected to positive outcomes related to mental health and well-being. However, the psychological mechanisms that account for these relationships are largely unknown. A multiple-step multiple mediator structural equation modeling (SEM) model was tested with mindfulness as the independent variable; purpose in life and behavioral activation as serial mediators; and happiness, anxiety, and depression as outcome measures. Data were obtained from 1267 women. Higher mindfulness was associated with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…The negative association between the variables of well-being and depression is expected and previously reported (Crego et al, 2021 ; Crumbaugh & Henrion, 1988 ; Crumbaugh & Maholick, 1964 ; Deci & Ryan, 2012 ; Hedberg et al, 2010 ; McKnight & Kashdan, 2009 ; Reilly et al, 2019 ). The reason for these results may be due, as previously stated, to the positive reinforcing power of the purpose, its character as a discriminative stimulus for action, its association with reinforcing activities, and its role in modifying the function of stimuli, making the organism less influenced by the aversive stimuli of the environment (Harte & Barnes-Holmes, 2021 ; Kissi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The negative association between the variables of well-being and depression is expected and previously reported (Crego et al, 2021 ; Crumbaugh & Henrion, 1988 ; Crumbaugh & Maholick, 1964 ; Deci & Ryan, 2012 ; Hedberg et al, 2010 ; McKnight & Kashdan, 2009 ; Reilly et al, 2019 ). The reason for these results may be due, as previously stated, to the positive reinforcing power of the purpose, its character as a discriminative stimulus for action, its association with reinforcing activities, and its role in modifying the function of stimuli, making the organism less influenced by the aversive stimuli of the environment (Harte & Barnes-Holmes, 2021 ; Kissi et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
“…Among them, the variables of purpose and those of social support have theoretical and factual relevance. Although the emergence of theorizations about meaning and purpose in psychology initially had a strong speculative and reductionist character (Frankl, 1949/ 1991 ), later, various approaches managed to support both theoretically and empirically the relevance of the concepts of meaning and purpose as salutogenic variables in psychology and psychiatry (Crego et al, 2021 ; Crumbaugh & Henrion, 1988 ; Crumbaugh & Maholick, 1964 ; Deci & Ryan, 2012 ; Hedberg et al, 2010 ; McKnight & Kashdan, 2009 ; Reilly et al, 2019 ) And in the context of the current pandemic (Karataş & Tagay, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the connection between mindfulness and anxiety, stress, and depression through mediating variables has been highlighted by some empirical studies (e.g., Crego et al, 2021 ; Pérez-Aranda et al, 2021 ). Crego et al ( 2021 ) found that the relationship between mindfulness and each of the outcome variables, including anxiety and depression is partially mediated by behavioral activation and purpose in life. Pérez-Aranda et al ( 2021 ) reported that resilience partially mediates the influence of mindfulness and self-compassion on depression.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Purpose in life can also act as a protective factor in relation to mental health (Galek et al, 2015;Aghababaei et al, 2016;Glaw et al, 2017), well-being (Stoyles et al, 2015), and happiness (Aghababaei and Błachnio, 2014). Those who exhibit a strong sense of purpose in life also express greater self-esteem (Błażek and Besta, 2012) and happiness (Crego et al, 2021), and less depression (Hartanto et al, 2020). In a study carried out among Chinese emerging adults, examined the effects of purpose in life with various variables in relation to mental health.…”
Section: Purpose In Life In Relation To Other Study Constructsmentioning
confidence: 99%